2000
DOI: 10.1007/pl00008845
|View full text |Cite
|
Sign up to set email alerts
|

Density compensation in neotropical primate communities: evidence from 56 hunted and nonhunted Amazonian forests of varying productivity

Abstract: Density compensation is a community-level phenomenon in which increases in the abundance of some species may offset the population decline, extirpation, or absence of other potentially interacting competitors. In this paper we examine the evidence for density compensation in neotropical primate assemblages using data from 56 hunted and nonhunted, but otherwise undisturbed, forest sites of Amazonia and the Guianan shields from which population density estimates are available for all diurnal primate species. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
0
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(224 citation statements)
references
References 52 publications
5
202
0
9
Order By: Relevance
“…The study area is characterized by two distinct seasons, one dry season (November to March) and one wet season (April to October) with a peak of rainfall from June to August. Rainfall averages 3000 mm yr 21 , and humidity is high (rarely less than 90%) with daily temperatures ranging from 158C to 338C, with minor seasonal differences.…”
Section: Materials and Methods (A) Study Sitesmentioning
confidence: 99%
“…The study area is characterized by two distinct seasons, one dry season (November to March) and one wet season (April to October) with a peak of rainfall from June to August. Rainfall averages 3000 mm yr 21 , and humidity is high (rarely less than 90%) with daily temperatures ranging from 158C to 338C, with minor seasonal differences.…”
Section: Materials and Methods (A) Study Sitesmentioning
confidence: 99%
“…The aforementioned tree studies were conducted in the Western Amazon where soils are all geologically young; however, tree species composition changes more rapidly from the Western to the Central Amazon than along a North-South gradient within the Western Amazon (Steege et al 2000). Several other studies have suggested that the geological age (translates into nutrient availability) of the Amazon may affect regional productivity which in turn affects the local community composition (Emmons 1984, Peres 1997, Peres & Dolman 2000, Radtke et al 2007, Stouffer 2007. Species may be adapted for limited productivity in the old Amazon and elevated levels of productivity in the young Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is ideal to measure the intensity of each response variable directly, many researchers use subjective measures or expert knowledge of anthropogenic disturbances in conservation biology (Bojorquez-Tapia et al, 2003;Ricketts and Imhoff, 2003;Ricketts et al, 1999) because of the difficulties in accurately measuring some variations, such as hunting pressures or a lack of time to conduct exhaustive scientific research or both (Davis et al, 1990). For example, Peres and Dolman (2000) used subjective measures of primate hunting pressures over a 100-yr period for 56 sites in Brazilian Amazonia. To reduce inaccuracies inherent in the subjective measures (Bojorquez-Tapia et al, 2003), only Lehman estimated intensities of anthropogenic disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce inaccuracies inherent in the subjective measures (Bojorquez-Tapia et al, 2003), only Lehman estimated intensities of anthropogenic disturbances. Following Peres and Dolman (2000), we used a 4-point intensity scale at each site:…”
Section: Methodsmentioning
confidence: 99%